Pengaruh Rebusan Daun Mint Dan Rebusan Jahe Untuk Menghilangkan Mual Muntah Pada Ibu Hamil Trimester 1 Di Puskesmas Tanjung Agung - Jusmawati; Meilyta , Dewi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The World Health Organization states that 14 percent of pregnant women experience vomiting and nausea during pregnancy. In the first trimester of pregnancy, around 73.5 percent of pregnant women in the United States, Australia and five European countries reported experiencing morning sickness. In Indonesia, 50 to 75 percent to 85% of pregnant women report experiencing nausea (Eka, 2023). During the first trimester of pregnancy, nausea and vomiting, known as emesis gravidarum, are very common. Although nausea and vomiting are more common in the morning, a condition called